Development and Validation a Nomogram for Predicting Overall Survival in Patients With Intrahepatic Cholangiocarcinoma - Yuan, Chen; Hu, Zhigang; Wang, Kai; Zou, Shubing (Frontiers in Surgery, 2021)
Background: To establish an effective nomogram to predict the overall survival of patients with intrahepatic cholangiocarcinoma (ICC). Patients and Methods: Data used to build the nomogram comes from the Surveillance, Epidemiology, and End Results (SEER) database. Patients diagnosed with ICC between 2005 and 2016 were retrospectively collected. Prediction accuracy and discrimination ability of the nomogram was evaluated by concordance index(C-index) and calibration curve. The area under receiver operating characteristic (ROC) curve (AUC) and decision curve analysis (DCA) to compare the precision of the 1-,3-and 5-year survival of the nomogram with 8th AJCC TNM staging system. Finally, it was verified in a prospective study of patients diagnosed with ICC in the Second Affiliated Hospital of Nanchang University from 2014 to 2020 by bootstrap resampling. Result: The study contains two parts of data, we establish a nomogram using external data, and we conducted internal verification and external verification. The nomogram we have established has good calibration, with a concordance index(C-index) of 0.75(95%CI,0.74 to 0.76) for OS prediction. The AUC value of the nomogram predicting 1-,3- and 5-year OS rates were 0.821,0.828 and 0.836, which were higher than those of 8th AJCC TNM staging systems. The calibration curve for probability of survival between prediction by nomogram and actual observation shows good agreement. The nomogram showed better accuracy than the 8th edition AJCC TNM staging. Conclusion: The nomogram established can provide a more accurate prognosis for patients with intrahepatic cholangiocarcinoma.